Persepsi dan Pengalaman Kepemimpinan Pendidikan Dalam Meningkatkan Mutu Pelayanan - Wulan Kurnia Sari; Ivan Riyadi; Noval Maliki; Jatim Desiyanto; Fajar Man; Afiq Fikri Almas; Mahin Ainun Naim (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research is entitled Perceptions and Experiences of Educational Leadership in Improving Service Quality. This research aims to explore the perceptions and experiences of educational leadership in controlling educational services. Using qualitative methods, this research involved interviews. The data obtained was analyzed using thematic analysis techniques to identify main themes related to educational customer satisfaction, challenges and expectations for service quality. The research results show that the majority of customers are educational. The number of educational institutions that do not provide good service affects educational customer satisfaction. As a result, the acceptance of new students continues to decline, leading to schools being merged or closed because the number of students does not meet the ceiling. For this reason, it is necessary to improve the quality of service in educational marketing management in educational institutions